KETAHANAN 62 JENIS KAYU INDONESIA TERHADAP PENGGEREK KAYU DI LAUT - Mohammad Muslich; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Sixty two Indonesian wood species were exposed to marine borers for determining their resistances. The study was conducted at Rambut Island seashore using wood samples measuring 2,5 cm by 5 cm by 30 cm. The samples were randomly arranged using nylon rope immersed in the shore and then observed after six months. Results revealed that most of the samples were completely attacked by Martesia striata Linne of the Pholadidae family, Teredo bartchi Clapp., Dicyathifer manni Wright and Bankia cieba Clench., of the Teredinidaefamily. Nine out of 62 wood species i.e. 14.5% were resistant to marine borers. Eusideroxylon zwageri T. et B., was classified as very resistant (no attack), while Diospyros celebica Bakh., Mimusops elingi L., Parinari corymbosa Miq., Tectona grandis lf, Trestania maengayi Duthii.,Trestania whiteana Griff, Vitex cofassus Reinw., and Vitex pubescens Vahl. were categorized as resistant (light attack). These nine wood species are suitable for marine constructions.